Planning and practices of Chinese Eco-development: a case study of Chongming Eco-Island - Xie, Linjun (2019)
Since the turn of the twenty-first century, eco-developments as experimental solutions to create sustainable pathways for a harmonious relationship between humans and nature have begun to unfold in China. This research argues that there is a gap in the analysis of current eco-development in China in which insufficient attention is given to the shaping and reshaping dynamics of an eco-development project throughout time, and different stakeholders’ roles and perceptions in the planning and practices of an eco-development. Integrating both empirical and methodological insights from ecological modernization and political ecology, this research aims to critically evaluate Chinese eco-development as a whole from design, through delivery, and to local effects. An integrative approach allows a more fruitful understanding of the local dynamics and complexities of Chinese eco-development from both a top-down perspective that dissects the formation and implementation of strategic policies and planning initiatives, and a bottom-up view that explores local individual and community’s perceptions of and responses to eco-development. The research is founded on an intensive case study of Chongming Eco-Island in Shanghai, China. The analysis is built upon data collected through archival research, in-depth semi-structured interviews with both state and non-state actors, focus group meetings with local communities, and on-the-ground observation and documentation. The findings of this research show that despite a welcome transformation from the previous pro-growth ideology and practices to a more ecology-centric construction, eco-developments on Chongming have been driven by strategic entrepreneurial planning of the Shanghai municipal state and by quantitative targets that are designed to address primarily the city’s overall development needs. Privileging an ecological modernization thinking and largely excluding local knowledge and concern, eco-developments on Chongming instead of promoting local sustainable development, generates unintended and adverse results for the local environment and the community. This research contributes to debates on Chinese eco-development by formulating an integrative framework to allow a holistic examination of local eco-development planning, practices and effects, and to investigate the views and values of both state and non-state actors. This research also provides an attractive alternative strategy for those seeking to analyse a more nature-focused, locally-relevant means to promote urban sustainability planning and development.